Construction of the tetracyclic core of the Lycopodium alkaloid annotinolide C. Issue 11 (26th March 2021) - Guo, Xiang; Li, Yong-Yao; Wang, Shuang-Hu; Zhang, Fu-Min; Li, Bao-Sheng; Tu, Yong-Qiang; Zhang, Xiao-Ming
Abstract : A concise approach to the tetracyclic core of annotinolide C has been developed which contains two key reactions epoxidation/1, 2-migration to construct an aza [6.5] spiro ring (A and B) and semireduction/cyclization to construct lactone ring D. Abstract : A concise method of synthesizing the tetracyclic core of annotinolide C has been developed. The key steps include a tandem epoxidation/semipinacol rearrangement step to construct a quaternary aza [6.5] spiro ring (rings A and B), an intramolecular aldol reaction to assemble a [3.2.1] bridged ring system, and tandem semireduction/lactonization to form a five-membered lactone D-ring.